Storytelling, humour, and promotions: How social media marketing influences university students' green purchase intention - Cai, Jinchi; Osman, Syuhaily; Haron, Sharifah Azizah; Teng, Wenqing (Elsevier, 2025)
This study explains how social media information sources, formats, and promotions affect Chinese university students' inclinations to engage with social media and make environmentally friendly purchases. Multivariate analysis of variance (MANOVA) was used to validate Study 1, analysis of variance (ANOVA) was used to validate Study 2, and PROCESS Model 4 was used to evaluate the mediation functions of attitude and conceptual fluency. The results indicate that firm-generated content (FGC) is more effective than user-generated content (UGC) in terms of university students' engagement - specifically liking (L), sharing (S), and commenting (C) - as well as in fostering green purchase intentions (GPI), particularly with firm-generated storytelling content (FGCS). The mediating role of attitude demonstrates partial or full mediation, except for firm-generated humour content (FGCH), which did not show a significant effect on GPI, but the two promotional modes are not significant difference, however, through the mediating effect of Concept Fluency (CF), half-price promotions can greatly increase the impact of FGCS and FGCH on GPI. This research (1) contributes to the body of knowledge already available on social media UGC versus FGC, and (2) illustrates how social media content type and provider affect consumers' intentions to make green purchases, and (3) illustrates the influence of branded content and promotional strategies on university student consumers. Overall, this study enables businesses to better understand how forms of green content marketing and promotional models can engage university students’ consumers in social media interactions and generate green purchase intentions.